Use of Antibiotic and Gut Microbiota Dysbiosis: Role of Immune Function in Iraqi Children - Al-ma’amouri, May Y.; Alkhazraji, Zeena Jamal (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Antibiotic use and its abeyant effect on gut microbiota dysbiosis are key issues for Iraqi children's immune function. The equilibrium of gut microbiota is vital for immune system modulation, the development of a strong defense adjoin infections, and the abstention of autoimmune diseases. Misuse or inappropriate use of antibiotics, which is usually acquired by factors such as infections repetition or cultural practices, can agitate this antithesis and aftereffect in dysbiosis. The aim of this investigation is to acquisition out how frequently antibiotics are acclimated in Iraqi children and whether this use is associated to abnormalities in their gut microbiome. We additionally aim to investigate how these disturbances may aftereffect these children's allowed function. Materials and Methods: 70 Iraqi child in age range (2-8) have been involved in cross sectional study to assess the effect of antibiotics on both gut dysbiosis and immune. Results: This study shows that the sample has a gender imbalance, with more women than men, and modest age variety. Of the total population, 55.72% live in cities, 88.57% report having no health issues, with asthma being the most common at 5.71%. The frequency of antibiotic usage has a major effect on gut bacteria; higher use is associated with fewer helpful species and more dangerous ones.